2018
DOI: 10.14744/anatoljcardiol.2017.8079
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ethanol increases calcium/calmodulin-dependent protein kinaseIIδ gene expression and decreases monoamine oxidase amount in rat heart muscles: Rescue effect of Zingiber officinale (ginger) extract

Abstract: Objective:Association between chronic alcohol intake and cardiac abnormality is well known; however, the precise underlying molecular mediators involved in ethanol-induced heart abnormalities remain elusive. This study investigated the effect of chronic ethanol exposure on calcium/calmodulin-dependent protein kinase IIδ (CaMKIIδ) gene expression and monoamine oxidase (MAO) levels and histological changes in rat heart. It was also planned to find out whether Zingiber officinale (ginger) extract mitigated the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Our recent works and several others indicated that the overexpression of the predominant cardiac isoforms of CaMK including CaMKIIδ1 and CaMKIIδ2 is one of the hallmarks of molecular alteration that induces myocardial hypertrophy and heart failure (18)(19)(20)(21). In addition, the association between CaMKIIδ isoforms expression alteration and shifts in cardiac function has been reported in pathologic conditions such as dilated cardiomyopathy, myocardial infarction, arrhythmia, and heart failure upon injuries such as pressure overload and ischemia-reperfusion (22)(23)(24).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our recent works and several others indicated that the overexpression of the predominant cardiac isoforms of CaMK including CaMKIIδ1 and CaMKIIδ2 is one of the hallmarks of molecular alteration that induces myocardial hypertrophy and heart failure (18)(19)(20)(21). In addition, the association between CaMKIIδ isoforms expression alteration and shifts in cardiac function has been reported in pathologic conditions such as dilated cardiomyopathy, myocardial infarction, arrhythmia, and heart failure upon injuries such as pressure overload and ischemia-reperfusion (22)(23)(24).…”
Section: Discussionmentioning
confidence: 92%
“…Total RNA was extracted using an extraction kit (Gene All, South Korea), according to the manufacturer's protocol. The real-time quantification of the target genes was carried out as described previously in our earlier study (17,18). Reverse transcriptase (RT) was presented using Hyperscript™ Reverse Transcriptase (Gene All, South Korea).…”
Section: Quantitative Real Time Pcr and Rt-pcrmentioning
confidence: 99%
“…In addition, one CAMK2D genetic variant (rs3815072) is significantly associated with pathological gambling [ 35 ]. CAMK2D is also overexpressed with ethanol exposure in rats [ 36 ]. In addition, gene expression of CAMK2D, enriched in the cell cycle and the calcium signaling pathway, is associated with PCa metastasis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term alcohol exposure can lead to histopathologic changes in different organs [ 67 ]. In the lungs, there are alterations such as the enlargement and destruction of the air spaces, focal infiltration of the polymorphonuclear cells, an increase in the pneumocytes in the alveolar walls and fibrosis with damage to the lung structure, which was observed during experiments on rats.…”
Section: Pharmacological Properties Of Gingermentioning
confidence: 99%